Nonprofit Organizations : theory, management, policy - Anheier, Helmut K., 1954-; Toepler, Stefan (London: Routledge; Taylor & Francis, 2023)
"In this new edition of this popular textbook, Nonprofit Organizations: Theory, Management, Policy, Helmut K. Anheier and Stefan Toepler have fully updated, revised and expanded this comprehensive introduction to a growing field. The text takes on an international and comparative perspective, detailing the background and concepts and examining relevant theories and central issues. Anheier and Toepler cover the full range of nonprofit organizations - service providers, membership organizations, foundations, community groups - in different fields, such as arts and culture, health and social services, and education. Introducing central terms such as philanthropy, charity, social entrepreneurship, social investment, and civil society, they explain how the field relates to public management and administration. This textbook is systematic in its approach to theories, management, and policy. The first edition won the Best Book Award at the American Academy of Management in 2006, and this new edition will continue to match the growing demand for academic teaching. Nonprofit Organizations: Theory, Management, Policy is an ideal resource for students of both undergraduate and post-graduate courses"--
Revised editon of Nonprofit organizations, 2014.
Includes bibliographical references and index.
Keywords: Nonprofit organizations